(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: In Switzerland, psychiatric evaluations are crucial for deciding on eligibility of disability benefits for claimants with chronic widespread pain (CWP). However, the poor standardisation and low transparency of such evaluations have been criticised. Standardisation and transparency may be enhanced by comprehensive functioning documentation using the International Classification of Functioning, Disability and Health (ICF). We applied the ICF as a reference frame to determine a list of functioning aspects and contextual factors commonly reported in psychiatric work capacity evaluations of Swiss disability claimants with CWP. METHODS: We conducted a retrospective qualitative and quantitative content analysis of 24 psychiatric reports of claimants with CWP by using the ICF taxonomy and a personal factor categorisation for data coding. Coded categories were considered candidate items for standardised documentation in psychiatric evaluations involving CWP if they passed a predetermined threshold based on their relative frequency across reports. RESULTS: A total of 71 second level ICF and personal factor categories passed the threshold. In total, 21 categories referred to the ICF component personal factors, 19 to body functions, 18 to activities and participation, and 13 to environmental factors. CONCLUSIONS: The list of ICF and personal factor categories we determined in this study addresses concepts commonly reported in psychiatric evaluations of medical work capacity involving CWP. It can serve as a starting point in developing a standard for comprehensive functioning documentation in the present context.